(untitled) (Altre Modernità, 2020)
In this paper, I analyse the socio-cultural construction of dementia in mainstream contemporary English cinema. I consider dementia from the perspectives of individual forgetfulness and cultural silence and fear. Anglophone films, part of the broader Western culture of dementia, reveal both these perspectives in their portrayals of amnesic dementia patients and the recurring elements of silence and fear that surround them. At a biomedical level, a cure to dementia has not been found. At the cultural level—through language and cultural empowerment—a cure is attempted, following the flow of the ‘underground river of dementia’, as it surfaces and dives.